Microscopic study of AOT and CTAB anionic-rich catanionic phase - Chun, Yuan Tan; Kok, Siong Khoo; Shahidan Radiman,; Irman Abdul Rahman,; Nur Farhana bt Amari, (Universiti Kebangsaan Malaysia, 2014)
Catanionic system using anionic sodium bis-(2ethylhexyl)sulfosuccinate (AOT) and cationic cetyltrimethylammonium bromide (CTAB) is studied. The system is prepared by addition of CTAB solution to a prepared AOT solution until slight anionic-rich catanionic phase is produced. Catanionic system consists of the mixture of different types of surfactants and counterion due to electrostatic interaction between the oppositely charged surfactant. Both of these products affect the in surface activity of the surfactant. Hydrodynamic diameters decrease and clearer solution were seen with the increase of CTAB concentration in solution mixture. As a result, mixed surfactant with larger hydrophobic region and the presence of counterion will induce smaller vesicle to form in catanionic system.